Effectiveness of Farmers Field School for Integrated Pest Management in Tomato - George, S.; Hegde, M.R.; Balakrishana, B.; Khandekar, Nita (Indian Journal of Extension Education, 2010)
Farmers field schools (FFS) have emerged as effective transfer of technology tools for promotion IPM packages, as the experiences show in different countries. In this direction an effort was made by the Division of Extension and Training, Indian Institute of Horticultural Research (IIHR), Bangalore, to popularize the IPM package developed by II HR through Farmer Field School (FFS). A predominantly tomato growing village called Agrahara in Bangalore north taluk of Bangalore Rural district was selected for implementation of FFS. The objective was to convince the farmers about the philosophy of IPM and facilitate the identification and effective management of pest and diseases . The paper focuses on the impact of IPM in terms of reduction in pest and disease levels, effect on level of usage of chemicals and reduction in the cost of cultivation compared to farmer’s practice. The study found that through farmer FFS, IPM can be successfully implemented . There was significant reduction in the usage of chemicals and the knowledge of farmers was also substantially increased.